EXPLORING CONTEMPORARY INDIAN SOCIETY: THEMES AND NARRATIVES IN ARVIND ADIGA'S “BETWEEN THE ASSASSINATIONS” - Gahlawat, Anshu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper examines the collection of interconnected stories titled "Between the Assassinations" by Arvind Adiga, published in 2008. The paper explores the various themes and narratives presented in the novel, which provides a snapshot of life in the fictional town of Kittur on India's southwestern coast. The study delves into the captivating portrayal of contemporary India, focusing on themes such as caste discrimination, religious tensions, and the impact of urbanization on small towns. Through a comprehensive analysis of the novel, this research aims to shed light on the social, political, and cultural complexities depicted by Adiga, highlighting the struggles, dreams, and aspirations of diverse characters from different walks of life.